Phase trajectory run as a useful tool in axial-piston pump wear detection - Stojek, Jerzy (My University, 2010)
In this paper the possibility of phase trajectory use in detecting of axial piston pump damage was presented. The wear of main part of pump elements such as: rotor and swash plate have been studied. The phase trajectories were estimated from vibration signal measured on pumps body in third directions. In order to get quantitative specification of analyzed trajectory At/pi parameter was introduced. At the and the relation between At/pi parameter and the wear of the pumps parts have been set.

W artykule przedstawiono możliwość zastosowania metody trajektorii fazowych w procesie oceny stanu zużycia pompy wyporowej, na przykładzie wypracowania wybranych elementów składowych pompy: tarczy wychylnej i zespołu wirnika. Wykorzystano do tego celu przebiegi trajektorii fazowych, które obliczono z pomierzonych na korpusie pompy sygnałów wibracji w przypadku wyposażenia jej w uszkodzone elementy składowe. Dokonując parametryzacji wyliczonych trajektorii otrzymano ich ilościowe miary w postaci bezwymiarowych współczynników At/pi, które powiązano z wypracowaniem zespołu pompy.
Wykorzystanie przebiegu trajektorii fazowej do wykrywania zużycia pompy tłokowej
Mechanics and Control
Keywords: positive-displacement pump; signal analysis; pompa wyporowa; phase trajectory; trajektoria fazowa; analiza sygnałów; diagnostic of machines; diagnostyka maszyn